Estimation of measurement uncertainty of coliforms in drinking water according to ISO19036:2019 - ZHONG Wentao; LU Lin; LI Zheng; ZHOU Peihua; HONG Zhenbai; ZHOU Cong (Shipin yu jixie)
ObjectiveThis study aimed to estimate the measurement uncertainty of coliforms in drinking water according to ISO19036:2019.MethodsBy designing protocols, the technical uncertainty (utech), matrix uncertainty (umatrix) and distribution uncertainty (udistrib) were estimated respectively, and the combined uncertainty (uc(y)) and extended uncertainty (U) were calculated by combining the values of the three components.ResultsAfter estimating the measurement uncertainty of the second method of GB 4789.3—2016, the technical uncertainty was 0.120 2 log（CFU/mL）, the matrix uncertainty was 0.1 log（CFU/mL）, and the distribution uncertainty was 0.065 5 log（CFU/mL） and 0.026 1 log（CFU/mL）. When the result was 440 CFU/mL, the extended uncertainty was 0.34 log（CFU/mL）, expressed as （2.64±0.34） log（CFU/mL）.ConclusionAccording to ISO19036:2019, the estimation of measurement uncertainty for quantitative determinations of microorganisms in food is more scientific and convenient compared to current domestic standards.